Role of Brand equity in influencing purchase intention branded baby soap: A case study in Jaffna District, Sri Lanka - S, Kalaimahal; K, Kumaradeepan, (International Journal of Scientific Research and Management (IJSRM), 2019)
Many organization tries to achieve their organizational goals like profit maximization, high market share and survival. In market, consumers have certain expectation from the brands and trend to rely on brand as an indicator to purchase intention of brand choice, all the resources spend in wasted of each brand organizations. Therefore, this study about the Role of brand equity in influencing the purchase intention of branded baby soaps, which is one of the most competitive markets in Jaffna District Sri Lanka.200 questionnaires were collected from Jaffna District population. Data were analyzed and evaluated by univariate and bivariate techniques. For this study, only five branded baby soaps are considered such as pears baby Jhonson and Jhonson, baby Cheramy, Khomba baby and Kekulu. However, the main thing is the marketer want to identify that all these soaps brand equity positively in influencing the purchase intention devoid of Kekulu. For the reason, there are very low Kekulu soap buyers in the study area.Overall view the brand equity strong positively influence the purchase intention of Jhonson and Jhonson soap. Eventually, this report recommends some actions for improving the role of brand equity in influencing the purchase intention of branded baby soap market.